Konseptualisasi dan Skema Metafora Hatimelalui Pendekatan Semantik Kognitif - Sirait, Asnita (Universitas Katolik Parahyangan, 2021)
Metaphor is one of interesting objects to be research for its rich cognition and use. This study aims at investigating the conceptualization of heart metaphors and to describe the image schemas of heart metaphors. The data of the study were collected from Corpus of Contemporary American English (COCA) which provides significant data relevant to the study. This is a literature study using a qualitative descriptive study through the framework of the Conceptual Metaphor Theory (CMT) proposed by Lakoff and Johnson. After the selection of metaphorical expressions of heart, the analysis was conducted to categorize the conceptual metaphor of each selected data. The image schemas were then drawn in accordance to the concept given. The study found that people mainly use metaphors to state these three types of concepts of heart metaphors, they are; HEART IS A CONTAINER, HEART IS AN OBJECT, and HEART IS HUMAN/BEING. These main concepts were then elaborated into several smaller categorizations. There are three image schemas drawn in accordance to the types of the conceptual metaphors like containment schema, compulsion schema, and removal of restraint schema. Then, image schemas are helpful to draw the mapping of abstract thing of target domain into more concrete thing of target domain.